2017
DOI: 10.1016/j.epsr.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Rational consumer decisions in a peak time rebate program

Abstract: A rational behavior of a consumer is analyzed when the user participates in a Peak Time Rebate (PTR) mechanism, which is a demand response (DR) incentive program based on a baseline. A multi-stage stochastic programming is proposed from the demand side in order to understand the rational decisions. The consumer preferences are modeled as a risk-averse function under additive uncertainty. The user chooses the optimal consumption profile to maximize his economic benefits for each period. The stochastic optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The consumer's expected marginal utility is a function of the baseline report f , because the consumption q is a function of f . For example, if the consumer is participating in the DR program and is signaled, then its consumption is q b (f, θ) which solves the implicit equation (12) and does depend on f . The following theorem establishes the optimality condition for the optimal baseline report f * in terms of M (f ), Theorem 1.…”
Section: B the Optimal Baseline Reportmentioning
confidence: 99%
“…The consumer's expected marginal utility is a function of the baseline report f , because the consumption q is a function of f . For example, if the consumer is participating in the DR program and is signaled, then its consumption is q b (f, θ) which solves the implicit equation (12) and does depend on f . The following theorem establishes the optimality condition for the optimal baseline report f * in terms of M (f ), Theorem 1.…”
Section: B the Optimal Baseline Reportmentioning
confidence: 99%
“…Case r i = 0 follows from Definition 3. Case r i = 1 is derived from optimality conditions of problem (2) at each interval of G(q i ; b i ), and selecting the global maximizer (see Vuelvas and Ruiz (2017)).…”
Section: Problem Statementmentioning
confidence: 99%
“…There are different ways to active DR in the electric power. Broadly defined, controllable programs (Diaz et al, 2017) and indirect methods (Vuelvas and Ruiz, 2017) are found as DR solutions, which are tools implemented by system operator (SO) to balance the demand with power generation by means of load modification. In particular, indirect methods are performed by changing energy price or giving an incentive payment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this paradigm poses some problems of consumer acceptance [15]. On the other hand, indirect methods are based on prices or incentive signals aimed to influence consumer behaviour (EV owners’ decisions) [16, 17]. The main advantage of this approach is that the infrastructure costs can be reduced [18], since it is a unidirectional approach.…”
Section: Introductionmentioning
confidence: 99%